Socio-philosophical analysis of symmetry and asymmetry - Ugli, Bekpulatov Ulugbek Rakhmatulla (Journal of Multidisciplinary Academic and Practice Studies, 2023)
Purpose: This study aims to examine the socio-philosophical significance of symmetry and asymmetry in shaping social structures and dynamics. Research methodology: A qualitative approach using philosophical analysis and comparative interpretation of classical and contemporary theories was employed. Results: The study finds that both symmetry (equality, justice, balance) and asymmetry (inequality, uniqueness, dynamism) coexist as fundamental forces in societal development, contributing to social cohesion and innovation. Conclusions: A harmonious balance between symmetry and asymmetry is essential for fostering sustainable social order, cultural inclusivity, and transformative progress. Limitations: The conceptual nature of the study limits its empirical generalizability; future research may incorporate data-driven validation. Contribution: This research offers a conceptual framework for understanding societal development through the dual lens of structural balance and dynamic change.